Dataset containing concentration of accumulated pollutants in 29 stormwater biofilters in the USA - Beryani, Ali; Furén, Robert; Flanagan, Kelsey; Österlund, Heléne; Lange, Katharina; Winston, Ryan J.; Tirpak, R. Andrew; Dorsey, Jay; Smith, Joseph; Viklander, Maria; Blecken, Godecke-Tobias; Department of Civil, Environmental and Natural Resources Engineering, Luleå University of Technology; et al. (Luleå University of Technology, 2024)
This dataset presents the concentrations of a wide range of stormwater pollutants accumulated in filter materials and forebays of 29 bioretention systems having been in long-term operation for urban stormwater treatment in Ohio, Michigan, and Kentucky (USA). The study investigates pollutants including metals, microplastics, and organic micropollutants (PAHs, phthalates, alkyl phenols, PCBs, as well as 35 PFASs and their precursors).

Denna datauppsättning presenterar koncentrationerna av ett brett spektrum av dagvattenföroreningar som ackumulerats i filtermaterial och förvägar i 29 bioretentionssystem som har varit i långvarig drift för rening av dagvatten i städer i Ohio, Michigan och Kentucky (USA). Studien undersöker föroreningar inklusive metaller, mikroplaster, och organiska mikroföroreningar (PAH, ftalater, alkylfenoler, PCB, såväl som PFAS och deras prekursorer).
Dataset innehållande koncentration av ackumulerade föroreningar i 29 dagvattenbiofilter i USA
Keywords: storm water; dagvatten; micro-litter; mikroskräp; runoff water; lakvatten (avrinnande); perfluorinated alkylated substances; PFAS; assaying; metals; water pollution; Organic micropollutants; Organiska mikroföroreningar; Fate and Transport; Öde och transport; TOP assay; TOP assay; Urban runoff; Stadens dagvatten; Filter media; Filtrera media; Bioretention; Bioretention; Environmental Sciences; Miljövetenskap; Construction Management; Byggprocess och förvaltning; Infrastructure Engineering; Infrastrukturteknik; Water Engineering; Vattenteknik